Endurance Exercise in Hypoxia, Hyperoxia and Normoxia: Mitochondrial and Global Adaptations - Przyklenk, Axel; Gutmann, Boris; Schiffer, Thorsten; Hollmann, Wildor; Strueder, Heiko K.; Bloch, Wilhelm; Mierau, Andreas; Gehlert, Sebastian (International Journal of Sports Medicine, 2017)
We hypothesized short-term endurance exercise (EN) in hypoxia (HY) to exert decreased mitochondrial adaptation, peak oxygen consumption (VO2peak) and peak power output (PPO) compared to EN in normoxia (NOR) and hyperoxia (PER). 11 male subjects performed repeated unipedal cycling EN in HY, PER, and NOR over 4 weeks in a cross-over design. VO2peak, PPO, rate of perceived exertion (RPE) and blood lactate (Bla) were determined pre- and post-intervention to assess physiological demands and adaptation. Skeletal muscle biopsies were collected to determine molecular mitochondrial signaling and adaptation. Despite reduced exercise intensity (P<0.05), increased Bla and RPE levels in HY revealed higher metabolic load compared to PER (P<0.05) and NOR (n.s.). PPO increased in all groups (P<0.05) while VO2peak and mitochondrial signaling were unchanged (P>0.05). Electron transport chain complexes tended to increase in all groups with the highest increase in HY (n.s.). EN-induced mitochondrial adaptability and exercise capacity neither decreased significantly in HY nor increased in PER compared to NOR. Despite decreased exercise intensity, short term EN under HY may not necessarily impair mitochondrial adaptation and exercise capacity while PER does not augment adaptation. HY might strengthen adaptive responses under circumstances when absolute training intensity has to be reduced.
Keywords: mitochondrial adaptation signalling; respiratory chain complexes; peak power output; peak oxygen consumption